2003
DOI: 10.1590/s0074-02762003000500003
|View full text |Cite
|
Sign up to set email alerts
|

[No Title Available]

Abstract: A survey was conducted in the hemodialysis population of the state of Tocantins, Brazil, aiming

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(3 citation statements)
references
References 37 publications
(51 reference statements)
1
2
0
Order By: Relevance
“…This is lower than studies conducted by Rawat 3,7,[9][10][11] Worldwide prevalence rate ranging from 4-15% for HBsAg in HD patients has been reported, whereas, in India it ranges from 3.4% to 45%. 4,12 We report 14.8% HBV positivity among HD patients which in agreement with the study conducted by Mittal et al (10.2%), Bhaumika et al (12.1%). 7,13 However, Rawat et al reported 7% HBV positivity and Saravanan et al reported 33.5% positivity in their studies.…”
Section: Discussionsupporting
confidence: 92%
“…This is lower than studies conducted by Rawat 3,7,[9][10][11] Worldwide prevalence rate ranging from 4-15% for HBsAg in HD patients has been reported, whereas, in India it ranges from 3.4% to 45%. 4,12 We report 14.8% HBV positivity among HD patients which in agreement with the study conducted by Mittal et al (10.2%), Bhaumika et al (12.1%). 7,13 However, Rawat et al reported 7% HBV positivity and Saravanan et al reported 33.5% positivity in their studies.…”
Section: Discussionsupporting
confidence: 92%
“…The prevalence of HCV infection in patients undergoing dialysis is persistently greater than that in the general population being endemic in haemodialysis (HD) units around the world, predominantly in Mediterranean and developing countries of the Middle and Far East. Nosocomial transmission of HCV infection has been reported to be a considerable route in modern hospital dialysis units, particularly during the outbreaks of infection [1][2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Nosocomial transmission of HCV and HBV is an important contributing factor to the spread of these viruses [97,98]. Despite various infection control procedures in HD patients' prevalence and incidence rates of HBV and HCV are still significant [99,100]. Studies have shown that strict aseptic measures can virtually eliminate HCV contamination, even in units with a high prevalence of HCV infection [101].…”
Section: Discussionmentioning
confidence: 99%